(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
Comparative research of melting of complexes cis-dichlordiamineplatinum and cis-dichlordiaminepalladium with DNA is carried out. It is revealed, that melting temperature – Тm of complexes of DNA with both compounds at low concentrations grows, while at increase of concentration of these compounds on the contrary, Тm decreases.